2019
DOI: 10.1002/jcc.26131
|View full text |Cite
|
Sign up to set email alerts
|

Development of Coarse‐Grained Force Field by Combining Multilinear Interpolation Technique and Simplex Algorithm

Abstract: A fast, reasonable, and transferable coarse-grained (CG) molecular dynamics force field (FF) is essential to combine experimental and simulation data. However, the parameterization of CG FF usually requires massive computation, which hinders its rapid development. Here, we presented an efficient optimization protocol by combining multilinear interpolation technique with simplex algorithm. In this preliminary work, taking the experimental properties as the benchmark, we constructed a new set of CG FF for water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 138 publications
(172 reference statements)
0
16
0
1
Order By: Relevance
“…Nonbonded interactions are excluded for beads separated by one bond to avoid offset in L b . 35 Dihedral interactions in hydrocarbons and lipids are not introduced in the present work. We found that the inclusion of dihedral only improved the agreement of dihedral angle distributions with AA MD but had little impact on the thermodynamic properties and raised additional computation cost instead.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonbonded interactions are excluded for beads separated by one bond to avoid offset in L b . 35 Dihedral interactions in hydrocarbons and lipids are not introduced in the present work. We found that the inclusion of dihedral only improved the agreement of dihedral angle distributions with AA MD but had little impact on the thermodynamic properties and raised additional computation cost instead.…”
Section: Methodsmentioning
confidence: 99%
“…The computational details can be found in our previous work. 35 Properties of membranes. Both the structure and thermodynamic properties of dimyristoyl phosphatidylcholine (DMPC) and dipalmitoyl phosphatidylcholine (DPPC) membranes were evaluated using OPT1.35 FF.…”
Section: B Cg MD Simulationsmentioning
confidence: 99%
“…A local optimization was produced using the Nelder–Mead (simplex) algorithm, which is shown to be successfully applied for force field parameterization. Due to its stochastic nature, in contrast to gradient methods, it tends to be much less affected by low curvature of the cost function along with the “loose” degenerate collective modes, which would naturally occur in such a task. , Additionally, the final parameters obtained from several runs help to estimate the parameter dispersion and hence the degeneracy of the cost function with respect to collective modes, containing certain atomic parameters.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The Morse model potential [1], despite a very rough approximation, is widely used in molecular spectroscopy and in other areas of optics and chemical physics. According to the Chemical Abstracts Service, over 6,000 references are given on the request " Morse Formula" Ȧs an example, we present random selections of recent studies in the field of spectroscopy [2][3][4][5][6][7][8][9][10][11][12][13], the influence of an external field, laser dissociation of moleculescool [14][15][16][17][18][19][20][21][22][23][24], thermodynamics, kinetics [25][26][27][28][29][30][31][32][33][34], solid and liquid physicssti [35][36][37][38][39][40][41][42][43][44], intermolecular interactions [45][46][47]…”
Section: Introductionmentioning
confidence: 99%